What connects us in shared decision-making in health = Co nas łączy w podejmowaniu wspólnych decyzji o zdrowiu - Gheondea-Eladi, Alexandra (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This paper discusses the mechanisms that lead to consensus in shared decision-making (SDM) from a theoretical point of view. It considers the way in which SDM interventions are expected to share information, preferences and create shared mental representations in treatment decisions. It draws on consensus theory to argue that both content-based and process-based consensus are needed in SDM interventions in order to achieve an acceptable level of shared-ness.
Keywords: shared decision-making; consensus; training health professionals; wspólne decyzje; konsensus; kształcenie pracowników